Tinjauan Yuridis Tindak Pidana Pencucian Uang Dalam Tindak Pidana Korupsi di Indonesia - Yudhi Priyo Amboro; Fandias Fandias (Journal of Judicial Review, 2014)
Transactional political dynamics in Indonesia pushed formed eradicate corruption institutions namely the Corruption Eradication Commission. Political dynamics so well matched with the spirit of providing an efficient sanctions to corruption suspects with approved Law No. 25 of 2003 on Money Laundering. According to the former Head of the Financial Transaction Reports and Analysis, Yunus Husein, corruption has a close relationship with the alleged violation of Article of money laundering. It is given an advantage in a crime of corruption is frequently used for private purposes suspects.Methodology used in this research is normative juridical law-based comparative law. The data used in this research is secondary data obtained from the literature (library research). Once all the data is collected, then processed and analyzed to find legal issues become the object of study and conclude, then described descriptively.These results indicate that the sustainability of corruption has great potential, followed by other offenses for the crime of money laundering. It is in view of the circumstances that the amount of funds obtained in the transaction corruption.